Who Gets the Money? The Dynamics of R&D Project Subsidies in Germany - Birgit Aschhoff (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
The question of the allocation of public R&D funding is becoming particularly important when it comes to identifying the effects of state subsidies, in terms of input or output additionality. This analysis goes one important step further than the existing literature by including the time dimension. Using firm-level data on German manufacturing and knowledge-intensive service firms, this paper sheds light on the structure of the subsidy recipients over time. It turns out that participation in the funding scheme is quite stable. This is also confirmed by applying a multivariate approach. Firms having received funding in the past are more likely to be selected for public funding again. It is also important to control for the overall supply of subsidies. Besides, a firm's size and knowledge capabilities increase the probability of entering the scheme.
More recent version: http://hdl.handle.net/10419/27721
Keywords: H32; O38; C20; 330; R&D; Public Subsidies; Program Participation; Germany; Forschungssubvention; Projektfinanzierung; Industrielle Forschung; Wirtschaftspolitische Wirkungsanalyse; Innovation; Deutschland